2001
DOI: 10.1046/j.1365-2168.2001.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Suitability for endovascular aneurysm repair in an unselected population

Abstract: Only 30 per cent of unselected AAAs presenting to a vascular service are entirely suitable for EVAR; most of these patients can safely undergo open AAA repair. These data suggest that increased use of EVAR is only possible by deploying devices in suboptimal morphology, and in treating patients who would not normally be considered for open AAA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 18 publications
2
33
2
Order By: Relevance
“…Defining suitability for EVAR is a complex issue and is dependent on both manufacturer guidelines as well as individual clinician judgement. Numerous studies have shown varying degrees of suitability for EVAR, ranging from 25% to 75%; [118][119][120][121][122][123][124] however, most studies struggle when trying to collect data for a reliable consecutive series of patients with AAA. Suitability for EVAR at the proximal end of the device is predominantly dependent on having an adequately long aortic neck between the top of the aneurysm and the bottom of the lowest renal artery as well as a neck that is no more than approximately 2-3 cm in diameter, depending on which graft manufacturer is selected.…”
Section: Endovascular Aneurysm Repairmentioning
confidence: 99%
“…Defining suitability for EVAR is a complex issue and is dependent on both manufacturer guidelines as well as individual clinician judgement. Numerous studies have shown varying degrees of suitability for EVAR, ranging from 25% to 75%; [118][119][120][121][122][123][124] however, most studies struggle when trying to collect data for a reliable consecutive series of patients with AAA. Suitability for EVAR at the proximal end of the device is predominantly dependent on having an adequately long aortic neck between the top of the aneurysm and the bottom of the lowest renal artery as well as a neck that is no more than approximately 2-3 cm in diameter, depending on which graft manufacturer is selected.…”
Section: Endovascular Aneurysm Repairmentioning
confidence: 99%
“…Anatomic factors that influence suitability for EVAR include adequacy of vascular access for device introduction; aneurysm morphology; neck length and morphology; and iliac artery involvement (42)(43)(44)(45). Various series have suggested that there is considerable variability as to what percentage of patients will qualify for EVAR, depending on the criteria that are used to determine suitability (45,46).…”
Section: Indications and Contraindications For Evarmentioning
confidence: 99%
“…To assure optimal success with EVAR, each endoluminal device lists strict morphological criteria in its usage instructions. Using these guidelines, the suitability for EVAR has been reported to range from as low as 20% to as high as 60%, depending on anatomical criteria or device availability [11,12]. Endograft use outside of the Food and Drug Administration (FDA)-approved instructions for use has been associated with increased complication rates [13][14][15].…”
Section: Evar Versus Open Repair: Basic Variables In Aaa Management Dmentioning
confidence: 99%